2021
DOI: 10.3390/genes12050637
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Genetic Population Structure of Wild Red Foxes in Poland Reveals Low Risk of Genetic Introgression from Escaped Farm Red Foxes

Abstract: In this study we assessed the level of genetic introgression between red foxes bred on fur farms in Poland and the native wild population. We also evaluated the impact of a geographic barrier and isolation by distance on gene flow between two isolated subpopulations of the native red fox and their genetic differentiation. Nuclear and mitochondrial DNA was collected from a total of 308 individuals (200 farm and 108 wild red foxes) to study non-native allele flow from farm into wild red fox populations. Genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Microsatellite markers still remain an appropriate tool for first-stage exploration of the genetic diversity and the population structure of sheep [ 40 ] and animal populations [ 41 ]. The allelic diversity of the two dairy breed populations SS B and SS M was studied in terms of MNA, AR and P AR , as summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Microsatellite markers still remain an appropriate tool for first-stage exploration of the genetic diversity and the population structure of sheep [ 40 ] and animal populations [ 41 ]. The allelic diversity of the two dairy breed populations SS B and SS M was studied in terms of MNA, AR and P AR , as summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Domesticated mammals are not separated from their wild ancestors by strong reproductive barriers, and therefore they are likely to cross-breed in regions where their ranges overlap. Introgression of domesticated species’ alleles to wild species’ gene pool may threaten the genetic integrity of wild species [ 154 ], and therefore it is typically considered as a negative process. However, such introgression may increase the genetic variability in wild species suffering the effects of a severe bottleneck, and/or accelerate the process of adaptation to changing environmental conditions by providing novel genetic variation [ 155 ].…”
Section: Discussionmentioning
confidence: 99%
“…This category includes studies that have not found any signs of hybridization in the populations studied or found only very limited evidence e.g., [ 154 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 ]. We found 24 studies that fitted this category.…”
Section: Discussionmentioning
confidence: 99%